Gabapentin alleviates chronic spontaneous pain and acute hypoxia‐related pain in a mouse model of sickle cell disease. (27th June 2019) - Sadler, Katelyn E.; Langer, Sarah N.; Menzel, Anthony D.; Moehring, Francie; Erb, Ashley N.; Brandow, Amanda M.; Stucky, Cheryl L.
Summary: Pain is the main complication of sickle cell disease (SCD). Individuals with SCD experience acute pain episodes and chronic daily pain, both of which are managed with opioids. Opioids have deleterious side effects and use‐associated stigma that make them less than ideal for SCD pain management. After recognizing the neuropathic qualities of SCD pain, clinically‐approved therapies for neuropathic pain, including gabapentin, now present unique non‐opioid based therapies for SCD pain management. These experiments explored the efficacy of gabapentin in relieving evoked and spontaneous chronic pain, and hypoxia/reoxygenation (H/R)‐induced acute pain in mouse models of SCD. When administered following H/R, a single dose of gabapentin alleviated mechanical hypersensitivity in SCD mice by decreasing peripheral fibre activity. Gabapentin treatment also alleviated spontaneous ongoing pain in SCD mice. Longitudinal daily administration of gabapentin failed to alleviate H/R‐induced pain or chronic evoked mechanical, cold or deep tissue hypersensitivity in SCD mice. Consistent with this observation, voltage‐gated calcium channel (VGCC) α2 δ1 subunit expression was similar in sciatic nerve, dorsal root ganglia and lumbar spinal cord tissue from SCD and control mice. Based on these data, gabapentin may be an effective opioid alternative for the treatment of chronic spontaneous and acute H/R pain in SCD.